Year Four Pupils’ Performance in Solving Word Problems and School-type Difference - Chew Cheng Meng, Chin Huan, Menaga Suseelan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this study were to profile Year Four pupils’ performance in solving word problems involving perimeter formulae and determine whether there is a significant difference in their performance in terms of school type. The sample of the study consisted of 600 pupils from three types of primary schools in Penang, Malaysia, that is 200 pupils from National School (NS), Chinese National-Type School (CNTS) and Tamil National-Type School (TNTS) each. The results showed that the NS (M = 5.20) and CNTS (M = 6.70) pupils’ performance was in the average category while the TNTS (M =3.95) pupils’ performance was in the low category. The result of the Kruskal-Wallis H Test showed that there is a significant difference in their performance in terms of school type. The post-hoc test using Mann-Whitney U Test showed that there is a significant difference in their performance between NS and CNTS, NS and TNTS, and CNTS and TNTS.These results imply that mathematics teachers need to shift the focus of mathematics teaching and learning from procedural understanding itself to both conceptual and procedural understanding so that pupils can better understand and effectively solve word problems involving perimeter formulae in the primary schools